Analysis of sudden emergency intervention failures and their impact on patient safety during transportA descriptive and analytical study of the field work environment at the Saudi Red Crescent (The Review of Diabetic Studies, 2025)
This study aims to analyze the failures of sudden emergency interventions and their impact on patient safety during transport in the Red Crescent field work environment. The study adopted the descriptive analytical approach by applying a questionnaire consisting of ten items to a sample of (200) workers in ambulance services. The tool focused on four main areas, including: technical equipment malfunctions, training efficiency, level of communication during emergencies, in addition to psychological stress and workload. The results of the statistical analysis showed a high level of agreement regarding the existence of technical malfunctions that affect the quality of care during transport, and the results also showed a clear deficiency in continuous practical training. The results also indicated statistically significant relationships between the different axes, especially between technical malfunctions and lack of training. The study concluded that it is necessary to strengthen training programs, develop periodic maintenance protocols, and improve communication channels during emergencies, in order to raise the level of occupational and medical safety within the ambulance system.